Studi Alterasi Hidrotermal dan Mineralisasi Emas di Daerah Bukit Mas dan Kabir, Kecamatan Pantar, Kabupaten Alor, Provinsi Nusa Tenggara Timur - , MERCY DAUD SUMAA, ST ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Study area at Bukit Mas and Kabir is located in Pantar Island of Alor Regency, the province of East Nusa Tenggara. The research area is potential of economic ore deposits. The host rocks of volcanic rocks (dacite lava, tuff, andesite lava and volcanic breccia) are unconformable underlain by packstone and alluvium deposits. Wall rock alteration is dominantly controlled by geological structures, rock permeability and hydrothermal fluid. The altered rocks are classified into three zones. Advanced argillicis represented by secondary minerals of alunite, kaolinite, quartz and pyrite